Japan : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Japan has a universal public pension system. Social security spending is a key fiscal policy challenge in Japan. The 2004 pension reforms have increased the ratio of the government subsidy to the basic pension benefit. Three reform measures are necessary to improve pension finances: an increase in pension eligibility age, a reduction in the pension benefit, and an increase in contributions. Eliminating the preferential tax treatments of pension income and collecting pension contributions from dependent spouses could contribute to fiscal savings.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet